Explaining the Migration of Stocks from Exchanges in Emerging Economies to International Centers - Claessens, Stijn (World Bank, Washington, D.C., 2013)
The authors study the determinants of the growing migration of stock market activity to international financial centers. They use a sample of 77 countries and document that higher economic growth and more macroeconomic stability help stock market development. Countries with higher income per capita, sounder macroeconomic policies, more efficient legal systems, better shareholder protection, and more open financial markets tend to have larger and more liquid stock markets. The authors show that these factors also drive the degree with which capital raising, listing, and trading have been migrating to international financial centers. As fundamentals improve and technology advances, this migration will likely increase and domestic stock market activity may become too little to support local markets. For many emerging economies, the best policy is to establish sound fundamentals but not necessarily the trading, or even listing of securities locally.